A profile and training programme of psychological skills for track and field athletes - Lawless, F. J. (2013)
The purpose of this study was to compile a sport psychological skills profile of track and field athletes and to determine whether a purposefully-developed psychological-skills training (PST) programme would affect this profile and athletic performance. The study was conducted in two phases. During the first phase 143 student athletes completed sport psychological skills questionnaires before competing in the 2011 University Sport South Africa (USSA) Athletics Championship. The athletes` perceived importance of psychological skills, psychologically preparedness, and need for psychological skills training were investigated. The athletes` best performances at the championship were recorded and their IAAF performance points calculated. The majority of the athletes perceived PST as important. However, in contrast, a large percentage was uncertain about their need for PST programmes and, alarmingly, most of the athletes under-utilized the services of sport psychologists. This could possibly indicate a resistance to PST. Overall, the results revealed poor sport psychological skill levels. Only the achievement motivation and goal directedness dimensions showed satisfactory results. Effect sizes were used to compare the sport psychological skill levels of more and less successful athletes. This revealed significant differences between the respective groups. The within-group comparisons showed that the more successful sprinters outscored the less successful sprinters in the subscales of stress control and achievement motivation. Achievement motivation was the only aspect that differed significantly between the more and less successful middle and long-distance athletes. Among the jumpers, confidence and stress control distinguished between the top and bottom athletes. The more successful throwers recorded higher imagery and achievement motivation scores than the less successful throwers. The results from the first phase were used to develop a PST programme aimed at improving the sport psychological skill levels and performance of student track and field athletes. In Phase Two, athletes from Stellenbosch University were divided into an experimental (n = 24) and control group (n = 18). Both groups underwent pre and post-testing of the same psychological skills questionnaires used in the first phase, whilst their athletic performances were recorded on both occasions. The experimental group participated in a PST programme consisting of seven sessions which covered the following topics: achievement motivation, goal-directedness, managing somatic anxiety, managing cognitive anxiety, self-confidence, concentration, and imagery. In addition to these sessions daily activities and assignments were completed in a workbook. The effectiveness of the PST programme in improving the athletes` sport psychological skills levels is evident from the improvements observed in nine of the eleven subscales among the experimental group opposed to four skills among the control group. Inexplicably, the control group`s athletic performance improved significantly more than that of the experimental group. Further research into the role and effectiveness of PST in track and field is recommended.